Pengaruh Etika Kerja dan Stres Kerja Terhadap Kepuasan Kerja Karyawan - Manda Dwipayani Bhastary (Maneggio: Jurnal Ilmiah Magister Manajemen, 2020)
This study aims to determine and analyze the effect of work ethics on employee job satisfaction, the effect of job stress on employee job satisfaction and to determine and analyze the effect of work ethics and job stress on employee job satisfaction at PT. PLN (Persero) UIP3BS UPT Medan. The population in this study were all employees of PT. PLN (Persero) UIP3BS UPT Medan, amounting to 60 people. The sample technique used is saturated sample, thus the sample in this study were 60 employees of PT. PLN (Persero) UIP3BS UPT Medan. The data collection technique used was a questionnaire. The data analysis technique used is multiple regression. The results showed that there is a positive and significant influence of work ethics on job satisfaction, there is a negative and significant effect of work stress on job satisfaction, and there is an influence of work ethics and work stress on job satisfaction at PT. PLN (Persero) UIP3BS UPT Medan